Labour Market Dynamics and Labour Market Policies – Case Study Kosovo - Bellaqa, Bashkim (European Scientific Journal, ESJ, 2018)
Over the last decades, in Kosovo and in many Western Balkan countries, there have been processes of political, economic and social transformations. The object of this study was to analyse the linear trends, employment and unemployment correlation through Gross Domestic Production (GDP) and its growth, Consumer Prices Index (CPI), Import and the role of employment policies in Kosovo. The methods used for this study were: linear econometric models, correlation, comparative methods ect. Although there have been improvements in socio-economic indicators in Kosovo, the economy still has a higher unemployment rate compared to the countries of the region. The approach of linear relationships for econometric models is usually preferred to research the socio-economic situation and dynamics of labour market trends. Labour market analysis is a measurement unit and assesses the economic forces and demographics such as education and trainings on the one hand and employment on the other. According to the results conducted from the quantitative study, it turns out that the employment variable in Kosovo has a complex relationship with a set of other parameters where GDP and GDP change carries the main weight, etc.